LSP1 Gene rs3817198 Polymorphism and Breast Cancer Risk: A Systematic Review and Meta-analysis Study - Sanjari Moghaddam, Ali; Roodgar, Morteza; Mansourpour, Hamid; Mosavi Jarrahi, Alireza (Asian Pacific Journal of Cancer Biology, 2016)
In this meta-analysis, we tried to clear the relationship between breast cancer risk and LSP1 gene rs3817198T>C polymorphism. This meta-analysis was conducted according to PRISMA protocol. We searched PubMed/Medline, Web of sciences and EMBASE. All literature investigating the association of LSP1 gene rs3817198T>C and breast cancer risk were considered to include in the meta-analysis. We pooled ORs using both fixed and random-effect models. Egger’s test and funnel plot were used to evaluate Publication bias and small study effect. After evaluation and screening of citations, 14 publications were eligible for final analysis after applying of inclusion and exclusion criteria. Overall, 30,204 cases and 35,282 controls included in this meta-analysis. There was the significant association between LSP1 gene rs3817198T>C polymorphism and breast cancer only in homozygote genetic model (OR=1.14 [1.05-1.24]) and no association was found in heterozygotes (OR=1.03 [0.98-1.07]). The association was significant for popula ion-based studies and European & American & African population in both homozygote and heterozygote genetic model. There was no evidence of bias of literature and no small study effect. In conclusion, it seems that LSP1 gene rs3817198 polymorphism play its role in breast cancer incidence and other SNPs and environment are such triggers. Nevertheless, we recommend genome-wide association studies to evaluate the effect of SNPs in combination, not as single SNPs.